A predictive model for assessing the impact of the COVID-19 pandemic on the economies of some Eastern European countries - Marina Vasiljeva; Inna Neskorodieva; Vadim V. Ponkratov; N. V. Kuznetsov; Vitali Ivlev; Marina Ivleva; Maksim Maramygin; Angelina Zekiy (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The paper seeks to develop a predictive model for assessing the impact of the (COVID-19) pandemic on the economies of Eastern Europe, taking into account quarantine measures. Functions of the dependence on the number of the infected populations in Eastern Europe on pandemic duration were calculated based on trend analysis. Factors affecting the intensity of disease and the number of infected persons have been determined. Integral model of their influence has been built using regression analysis. Based on the values of the factors, the number of infected people and the rate of infection were predicted for each of the Eastern European countries. The prognostic duration of the stage of exponential disease growth and the total duration of quarantine (epidemiological saturation point) are substantiated. The predicted decline in Eastern European GDP due to COVID-19 has been estimated based on the construction of a prognostic regression model. The results obtained can be used by state authorities and economic agents as a tool for active and preventive response. They can also serve as an example of the urgent need to develop, especially in non-standard situations, mechanisms and products of open innovation.
Keywords: 650; COVID-19 pandemic; Eastern Europe; economy; export; import; open innovations; predictive model